(untitled) (Cambridge, UK, 2004)
This state-of-the-art book on how form is described in primate biology, and its consequences for function and behavior, includes contributions by internationally renowned researchers of quantitative primate evolutionary morphology. Each chapter elaborates upon the analysis of the form-function-behavior triad. The book is unique, therefore, not only in the diversity of the topics discussed, but in the range of levels of biological organization addressed--from cellular morphometrics to the evolution of primate ecology.
Keywords: Primates,Động vật linh trưởng,Primates,Động vật linh trưởng; Morphology,Hình thái học,Evolution,Tiến hóa